Translating health information into policy-making: A pragmatic framework. Issue 1 (January 2022) - Funk, Tjede; Sharma, Tarang; Chapman, Evelina; Kuchenmüller, Tanja
Highlights: Knowledge translation of health information has been little explored. Different tools facilitate knowledge translation of health information into policy-making. This framework supports efforts to increase integration of health information in policy-making. Abstract: Knowledge translation (KT) is increasingly acknowledged to have the potential to improve policy-making. The value of health information (HI), as part of the KT context, is now also increasingly understood. This paper aims to identify existing tools for the translation of HI into policy-making and to develop a related framework facilitating future application of these identified tools. Updating and building upon a scoping review undertaken for the Health Evidence Network (HEN) Synthesis Report No. 54, commissioned by the World Health Organization (WHO) Regional Office for Europe in 2017, a literature search was conducted using the same databases (PubMed and Scopus) and the same keywords as in the WHO/HEN scoping review. All papers elaborating on tools enhancing the use of HI in policy-making were included. Of the 2549 records screened, 17 publications were included in this study. This review identified four different types of tools: 1) Visualisation and modelling tools, 2) Information packaging and synthesis tools, 3) Communication and dissemination tools and 4) Information linkage and exchange tools. The distinctions between these are fluid as different tools can be combined or incorporated into one another to complement each other. Our framework shows that communication/dissemination or linkage tools are crucial to effectively inform policy decisions through HI. This study helps to understand and guide the processes of KT of HI.